(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
This paper presents a selection of unpublished small finds, belonging to pavements, yielded by excavations of the Università degli Studi of Milan at the ‘monumental complex’ of Tarquinia. They were found in secondary bed contexts, especially from the hypogeum of Sector O, used as a cistern, and can be related to mosaics previously found at the ‘monumental complex’, already published, and to others from other areas of the Civita Plateau. This contribution aims at updating studies in progress focused on such already known mosaics and improving knowledge of pavements in use in the ancient city during the Hellenistic and late-republican period.